Una escena de traducción en América Latina: “Las dos orillas” de Carlos Fuentes - Logie, Ilse (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In his short story “The two shores” the Mexican writer Carlos Fuentes (The Orange Tree, 1993) fictionalizes language contact. In this apocryphal rewriting of the chronicle of Bernal Díaz del Castillo, The True History of the Conquest of New Spain, the author puts translation on the centre stage by focusing on the ambiguous relations between the two top interpreters of Spanish con queror Hernán Cortés: Jerónimo de Aguilar and La Malinche. Besides, translation is also the genetic source of the story since it is itself an adaptation of an existing chronicle. In Fuentes’s version, Aguilar consciously distorts Cortés ’s words in order to reveal the con queror’s true intentions and to demonstrate his solidarity with the indigenous populations, the Aztecs and the Mayas. The story can be read as a reflection on the complex loyalties of translators and on lan guage ’s colonizing potential. It reconsiders the function of translation, which is presented as performative speech act rather than as a purely reproductive form of transfer. According to Fuentes, translation is an activity that is caught in a double bind as it harbors a potential for disruption and betrayal as well as for subversion.